ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DEVIDEN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013) (Students' Journal of Accounting and Banking, 2015)
This study aimed to examine the analysis of factors influencing the dividend policy. This study was conducted to examine the effect of Current Ratio, Debt to Equity Ratio, Growth, Collateralizable Assets and Return on Equity Dividend Payout Ratio on manufacturing companies listed in Indonesia Stock Exchange during 2011-2013. The data is obtained based on Indonesian Capital Market Directory (ICMD) and the Indonesia Stock Exchange (BEI) 2011-2013 publications using analysis unit manufacturing company.The population in this study are 151 companies listed in Indonesia Stock Exchange in 2011-2013. The sample selection was conducted using purposive sampling of 100 companies. Data testing technique is to use multiple linear regression analysis. The analysis showed that the variables Current Ratio, Collateral Assets, Return on Equity positive effect on dividend policy. While the Debt Equity Ratio, GROWTH negatively affect dividend policy.Keywords: Current Ratio, Debt Equity Ratio, Growth, Collateral Assets, Return on Equity, and Dividend Payout Ratio